100 anos de habitação mínima: ênfase na Europa e Japão - Caselli, Cristina Kanya (2008)
This work s objective is to survey and analyze the minimum housing designs developed during the 20th Century in various European countries, taking as counterpoint the designs made in Japan. The projects analysis considered: the spatial solutions, the dimensioning and the technology. The 20th Century was marked by many social, cultural and political changes that had influenced also the housing s architecture. Since the woman independence, and the costumes changes stimulated by the technical evolution, there was a true revolution into the communications with consequent reflexes in the human communities. The architecture didn t remain outside this avalanche of news however it came following these changes, thus adaptting the designs to the new persons needs. This master dissertation analyses the European and Japanese designs, in order to establish parameters for comparison among the various architectural parties adopted.